Resistance training performed with single and multiple sets induces similar improvements in muscular strength, muscle mass, muscle quality, and IGF-1 in older women: A randomized controlled trial - Cunha, Paolo M. (2020)
The purpose of this study was to compare the effects between single set vs. multiple sets of resistance training (RT) on measures of muscular strength, muscle mass, muscle quality (MQ), and insulin-like growth factor 1 (IGF-1) in untrained healthy older women. Sixty-two older women were randomly assigned to 1 of the 3 groups: single-set RT (SS, n = 21), multiple-sets RT (MS, n = 20), or nontraining control (CG, n = 21). Both training groups performed RT for 12 weeks, using 8 exercises of 10-15 repetitions maximum for each exercise. The SS group performed only 1 set per exercise, whereas MS performed 3 sets. Anthropometry, muscle strength (1RM tests), lean soft tissue (LST), and MQ from upper limbs (UL) and lower limbs (LL), and IGF-1 were measured before and after training. Both training groups showed significant pretraining to post-training increases for UL1RM (SS: 37.1%, MS: 27.3%, CG: 23.0%), LL1RM (SS: 16.3%, MS: 21.7%, CG: 20.7%), ULLST (SS: 7.8%, MS: 8.8%, CG: 21.1%), LLLST (SS: 5.6%, MS: 6.3%, CG: 20.8%), upper-limb muscle quality (SS: 25.2%, MS: 16.7%, CG: 20.2%), lower-limb muscle quality (SS: 10.5%, MS: 15.4%, CG: 23.5%), and IGF-1 (SS: +7.1%, MS: +10.1%, CG: 22.2%). We conclude that both SS and MS produce similar increases in muscular strength, LST, and MQ of upper and lower limbs, and IGF-1 after 12 weeks of RT in untrained older women. Our results suggest that, in the early stages, the RT regardless number of sets is effective for improving muscular outcomes in this population.